Urban image and environmental sustainability of lurín, peru: a bibliometric study - Yábar-Torres, Guisela (2024)
Environmental sustainability is central to the disciplines and activities, for this reason, this research aimed to develop lines and actions consistent with the objectives of sustainable development (SDG). It is thus urgent to assume strategies and tactics of citizen participation, as a source of citizen rights and duties, so research and actions along these lines support the objective of mitigating environmental impacts. The purpose of the study is to carry out a bibliometric analysis that allows investigation of the route of the urban image as a component of environmental sustainability to contribute to the quality of life. 1800 articles from the Scopus database published up to 2023 were analyzed. The data was standardized manually, using VOSviewer version 1.6.7, which allowed evaluating bibliometric indicators of the urban image as an important element of environmental sustainability, for which it was necessary to evaluate the contribution of countries, authors, and objects of study. Th e contribution of the countries that address the issue of urban image and environmental sustainability is signifi cant, led by China and followed by the United States of North America, due to the number of publications. The journals that disseminated the documents are of high quality according to diff erent metrics that account for their high impact. The urban image through its diff erent components, because it is not planned, has a negative impact on environmental sustainability, which is why it is urgent to promote Goal 11 of the SDGs, which proposes making cities and human settlements inclusive, safe, resilient and sustainable in Latin America and the Caribbean.